The Adjunctive Use of Half-Pin (Type I) External Skeletal Fixators in Combination with Intramedullary Pins for Femoral Fracture Fixation - Foland, Melissa A.; Schwarz, P. D.; Salman, M. D. (Veterinary and Comparative Orthopaedics and Traumatology, 1991)
A half-pin (type I) external skeletal fixator was used in conjunction with an intramedullary pin(s) for management of 29 femur fractures in 15 dogs and 14 cats. Eighty percent of the dogs and 100% of the cats achieved bony union using this combination of implants. However, because of the development of major complications which permanently impaired limb function (e.g. quadriceps tie-down), only 67% of the dogs and 93% of the cats were considered to have successful outcomes. The overall complication rate was 87% for dogs and 43% for cats. Dogs weighing <6.8 kg had a significantly lower complication rate than dogs weighing ≥6.8 kg. Dogs < one year of age were significantly more likely to develop a major complication resulting in an unsuccessful outcome, than dogs ≥ one year of age. A significant association was not established between any of the study variables and the complication incidence in cats.
Keywords: Fracture; intramedullary pin; external skeletal fixator